Production and characterization of bacterial cellulose by Leifsonia sp. CBNU-EW3 isolated from the earthworm, Eisenia fetida - Velmurugan, Palanivel; Myung, Hyun; Govarthanan, Muthusamy; Yi, Young-Joo; Seo, Sang-Ki; Cho, Kwang-Min; Lovanh, Nanh; Oh, Byung-Taek (Biotechnology and bioprocess engineering, 2015)
A total of five bacterial strains were isolated from earthworm, Eisenia fetida and examined for bacterial cellulose (BC) production in Hestrin-Schramm medium (HS). Among the five strains tested, CBNU-EW3 exhibited excellent BC production and was identified as Leifsonia sp. by 16S rDNA sequence analysis. BC production by Leifsonia sp. CBNU-EW3 was optimum at pH 5, 30°C, and with glucose and yeast extract as carbon and nitrogen sources, respectively, according to 15 day-long experiments. (XRD) analysis of the dried pellicle indicated that the BC was partially crystalline type I. Fourier transform infrared spectroscopy (FT-IR) analysis showed that the obtained pellicle contained the same functional groups as typical BC. Field emission scanning electron microscopy (FESEM) images showed that the BC micro-fibril matrix consisted of a flat surface with large pore size and cellulose aggregation.